Institutional Repository Perpustakaan Perguruan Tinggi (Studi Kasus di Perpustakaan Universitas Panca Bhakti) - Pajar Julhijah (THE LIGHT : Journal of Librarianship and Information Science, 2021)
The purpose of this study is to examine the problems contained in the Panca Bhakti University Library in building an Institutional Repository and to find out the stages in developing an Institutional Repository at the Panca Bhakti University Library. The method used in this research is descriptive analytical research method. The results obtained in this study were the finding of obstacles in building an Institutional Repository at the Panca Bhakti University Library, namely copyright, HR, and plagiarism issues. The steps taken by the Panca Bhakti University Library are analyzing the needs of its users, human resources that focus on the management of institutional repositories, facilities and infrastructure that increase capacity to support the implementation of activities in digital libraries, the last of which is the repository content providing scientific works from the academic community. Panca Bhakti University.